Movements, bandwagons, and clones: Industry evolution and the entrepreneurial process - Low, Murray B.; Abrahamson, Eric (Journal of Business Venturing, 1997)
Entrepreneurship research has paid insufficient attention to the context in which new businesses are started. Consequently, efforts to identify factors that consistently lead to entrepreneurial success have failed. This is because what works in one context will not necessarily work in another. Even worse, factors that lead to success in one context may lead to failure in another. This article addresses this problem by drawing from the concept of industry evolution to identify three broad but distinct organizing contexts—emerging, growth, and mature industries—and demonstrating how each context presents a different set of entrepreneurial challenges. An industry is defined not as a group of firms producing close substitutes, but instead, as a group of firms of the same organizational form. Industry evolution is understood therefore as the diffusion of an organizational form, with emerging, growth, and mature stages corresponding to the creation, exploitation and erosion of competitive advantage. Defining an industry in this manner makes it possible to overcome the problem of shifting industry boundaries and enables us to distinguish between entrepreneurial activities that shake up existing industries by creating new and competing organizational forms and entrepreneurial activities that replicate well-known organizational forms and drive an industry toward equilibrium. It also enables us to draw from the work of industrial organization economics, strategy, and population ecology. Entrepreneurship is defined as the creation of new organizations and is viewed as a context-dependent social process. New organizations are enacted as critical stakeholders change their behaviors in ways that allow the organization to emerge. The process is successful when the short-term existence of a new organization is no longer at risk. A typological theory of entrepreneurial success is developed by examining how the fit between context and four other critical dimensions cause successful foundings. The theory is multiplicative and probabilistic. It is multiplicative in that all dimensions need to fit for a founding to be successful. Poor fit in any one area can lead to failure. It is probabilistic in that the better the overall fit, the better the odds of success. In addition to context, the dimensions we examine are entrepreneurial networks, entrepreneurial confidence-building behaviors, the motivation of stakeholders, and organizational structures and strategies. In terms of entrepreneurial networks, we examine whether entrepreneurs have weak-tie or strongtie networks, and whether their networks are homogeneous or include subgroups that are unrelated. In terms of confidence-building behaviors, we explore the use of informal (e.g., repeated personal interaction) versus formal (e.g., contracts) mechanisms. With respect to stakeholder motivations, we ask whether stakeholders are driven by social or instrumental motivations. In terms of structure and strategy, we consider two issues. First, we explore whether the emerging organization is market or hierarchy based, and we consider the extent to which the organization is innovative versus imitative. We argue that these various dimensions come together in three logical configurations, that we label movements, bandwagons, and clones. EMERGING INDUSTRY ORGANIZING: MOVEMENTS Movements are the organizing processes through which new organizational forms are created. Pioneers of new forms of organizations have unique personal networks that enable them to see the potential of bringing the factors of production together in new combinations. They have strong ties to two or more nonoverlapping networks. To succeed, they must overcome problems associated with lack of legitimacy. Theentrepreneur is joined by highly committed stakeholders who are motivated by social factors. Belief in the venture's success is achieved through informal confidence building, such as incremental personal exchange and third-party reputation. In this manner, stakeholders develop personal familiarity with the form and make positive assessments about the entrepreneur's competence and trustworthiness. The organizing structure is market based with participant commitments being secured through flexible, cooperative agreements. The strategic emphasis is on innovation and experimentation. The belief in the importance and viability of the new organizational form serves as a loose ideology for controlling and coordinating the actions of participants. GROWTH INDUSTRY ORGANIZING: BANDWAGONS Bandwagons are organizing processes that seek to exploit the potential of a newly legitimated form. The strategic challenge at this stage is to prosper newly legitimated form. The strategic challenge at this stage is to prospeamidst rapid growth and change. The successful entrepreneur has an extensive network of high status individuals that can be tapped to quickly mobilize resources within a narrow window of opportunity. Stakeholders are motivated less by social factors, than by a desire to secure the benefits of being early movers. Formal confidence-building mechanisms dominate. In an effort to achieve efficiencies, develop sources of competitive advantage, and preempt the competition, more value-chain activities are developed in house. The strategic posture remains entrepreneurial; however, more emphasis is placed on following the example of other firms. MATURE INDUSTRY ORGANIZING: CLONES Clones are the organizing processes that replicate existing forms and incorporate all that has been learned about a given industry and type of business. Strong competition along with stable demand and technology make it difficult to find a source of competitive advantage in a mature industry. At this stage, the successful founder is someone with extensive industry knowledge and contacts who is capable of extracting operating efficiencies and/or identifying some underserved market segment. Expected returns are modest and stakeholders need to be motivated partly by social factors. However, the large amount of information now available about the form and the market itserves enables stakeholders to base their participation decisions on a rational assessment of expected future benefits. Given increased experience with the form, the relationships between the organization and its stakeholders are more predictable and as a consequence, subject to greater formalization. Models exist showing how to structure theserelationships, facilitating greater use of more specific contracts and guarantees. With tight margins and the need for efficiency, greater use is made of hierarchy in an attempt to manage costs. These same highly competitive conditions also make mistakes very expensive. The organization needs to draw upon the knowledge that others have learned about the form. Consequently, it adopts a more conservative strategic posture and is less likely to deviate from established practice. IMPLICATIONS FOR FUTURE RESEARCH If we are ever to understand what leads to entrepreneurial success, we must pay more attention to the context in which organizing occurs. Our typology suggests that fundamentally different processes may be at work at different stages of industry evolution. In addition to empirically testing our theory, an opportunity exists to reexamine the existing entrepreneurship literature through a new conceptual lens, asking how our interpretation of the research would differ if context was considered explicitly. Our theory also has the potential to inform questions about the role of organizational foundings in the diffusion of competitive advantage and to examine the impact of.founding conditions on long-term strategic adaptation.